Transdermal iontophoretic delivery of timolol maleate - Mayur Patni; Prashant Puranik; Aravind Sonawane; Prabhakar Panzade (Universidade de São Paulo, 2012)
Transdermal iontophoresis would be a promising method for the systemic delivery of water soluble and ionic drugs of relatively high molecular size, including peptides. The objective of the present study was to investigate the effect of biological variable such as guinea pig and human cadaver skin and other variables like drug concentration, current density on the transdermal iontophoretic transport of timolol maleate. The permeation profile of drug using solution and gel formulation was studied and compared. For better bioavailability, better patient compliance, and enhanced delivery, an iontophoretic drug delivery system of a timolol maleate matrix gel was formulated using Carbopol 974P. The study was conducted using silver-silver chloride electrodes across the guinea pig and human cadaver skin. Viscosity measurements and flux calculations indicated the suitability of the Carbopol 974P gel for transdermal iontophoretic delivery of timolol maleate. Anodal iontophoresis with silver-silver chloride electrode significantly increased the timolol maleate skin permeation as compared with the passive permeation study. The amount of timolol maleate transported during iontophoresis was significantly different among the different skins. However, iontophoretic gel formulations provided required flux of drug through human cadaver skin. A iontoforese transdérmica seria um método promissor para a liberação sistêmica de fármacos solúveis em água e iônicos de relativamente elevado tamanho molecular, incluindo peptídeos. O objetivo do presente estudo foi investigar o efeito da variável biológica, tais como cobaia e pele de cadáver humano, e outras variáveis como concentração do fármaco, densidade de corrente sobre o transporte transdérmico iontoforético de maleato de timolol. Comparou-se o perfil de permeação do fármaco usando a formulação de solução e de gel. Para melhor biodisponibilidade, melhor adesão do paciente e liberação aprimorada, formulou-se sistema de liberação iontoforética gel de maleato de timolol usando Carbopol 974P. O estudo foi conduzido usando eletrodos de prata-cloreto de prata na cobaia e na pele de cadáver humano. Medidas de viscosidade e de fluxo indicaram a adequação do gel Carbopol 974 P para liberação iontoforética transdérmica do maleato de timolol. A iontoforese anódica com eletrodo de prata-cloreto de prata aumentou significativamente a permeação dérmica do maleato de timolol, comparativamente à permeação passiva. A quantidade de maleato de timolol transportado durante a iontoforese foi significativamente diferente entre as diferentes peles . No entanto, as formulações iontoforéticas de gel forneceram o fluxo necessário do fármaco através da pele de cadáver humano.